Analisis Faktor Yang Berhubungan Dengan Perilaku Merokok Pegawai Pada Kawasan Tanpa Rokok (Ktr) Di Upt Pelatihan Kesehatan Dinas Kesehatan Provinsi Sumatera Utara Tahun 2020 - Farida Lumbantobing (Jurnal Kajian Kesehatan Masyarakat, 2020)
Government agencies are the order established in no-smoking areas but no-smoking areas are still difficult to realize because there are still many employees in government agencies who smoke. The implementation of no-smoking areas in the workplace is expected to have a positive effect to change smoking behavior, such as reducing smoking during working hours, smoking in special places and efforts to stop smoking. The study aims to analyze the factors associated with employee smoking behavior in non-smoking areas at UPT Health Training North Sumatera Provincial Health Office in 2020. The research uses mixed methods with combination of models or sequential explanatory design methods. The population is all 42 male employees. Quantitative sampling techniques uses total sampling methods and qualitative using purposive sampling method. Quantitative data analysis with univariate analysis, bivariate with chi square and multivariate and qualitative using the interview method. The results of quantitative study that there is a relationship between knowledge of the regulations on non-smoking areas (0,002), knowledge about the dangers of cigarettes (0,001), signs of smoking (0,001), supporting facilities and infrastructure (0,000), superiors' support (0,001), application of sanctions (0,000) ), the socialization of No-Smoking Areas (0.002) with smoking behavior of employees in no-smoking areas at UPT Health Training North Sumatera Provincial Health Office. And the conclusions of qualitative research that causes employees to smoke in areas without cigarettes is the lack knowledge of the employee about areas without cigarettes. It is recommended for employees to increase their knowledge about the dangers of cigarette content and knowledge of the No Smoking Area regulations.